Procoagulant effects of lung cancer chemotherapy on HUVEC, A549 cells, and monocytes. - Lysov, Zakhar (My University, 2012)
Cancer patients undergoing chemotherapy have an elevated risk for thrombosis. Although thrombosis is a common complication in cancer patients, the mechanisms of chemotherapy-induced thrombosis remain unclear. We investigated the procoagulant effects of lung cancer chemotherapy agents (carboplatin, paclitaxel, cisplatin, and gemcitabine) on endothelial cells, A549 cells, and monocytes. We also investigated the in vivo procoagulant effects of the aforementioned chemotherapeutic agents as well as the anti-angiogenic agent bevacizumab. Tissue factor (TF) activity, TF antigen and phosphatidylserine (PS) levels were measured on chemotherapy-treated human umbilical vein endothelial cells (HUVEC), A549 cells, and monocytes. Treatment of HUVECs, A549 cells, and monocytes with lung cancer single agent and combination chemotherapy resulted in significant increases in TF activity. However, only cisplatin- and gemcitabine- treated monocytes were found to have increased TF antigen levels. PS exposure was increased only on HUVEC and monocytes treated with cisplatin/gemcitabine combination therapy. Interestingly, addition of paclitaxel to carboplatin resulted in reduced levels of PS exposure on monocytes. This study is the first to explore the procoagulant effects of lung cancer chemotherapy agents on monocyte and A549 cell TF activity levels, as well as to investigate the mechanisms by which lung cancer agents may promote TF decryption on these cell lines. Our in vivo results demonstrated that treatment of healthy mice with bevacizumab, paclitaxel and carboplatin moderately increased plasma TAT levels in healthy mice. These studies reveal potential mechanisms by which lung cancer chemotherapy may increase the risk of thrombosis. These studies reveal potential mechanisms by which lung cancer chemotherapy agents induce a hypercoagulable state.
Keywords: Lung Cancer; Thrombosis; Chemotherapy; A549 cells; Coagulation; Endothelial Cells; Monocytes.; Circulatory and Respiratory Physiology; Circulatory and Respiratory Physiology